KECERNAAN SERAT KASAR KAMBING KACANG JANTAN PADA KONDISI LINGKUNGAN YANG BERBEDA DI LAHAN KERING KEPULAUAN - Bambang Hadisutanto; Bachtaruddin Badewi; Winda Wahyu Absari (Politeknik Pertanian Negeri Kupang, 2018)
Heat stress in goats is characterized by increased consumption of drinking water and decreased feed digestibility. The problem is whether the conditions of animal discomfort will affect the digestibility level of crude fiber and consumption of goat kacang water. The purpose of this study was to assess crude fiber digestibility and consumption of drinking water from goat kacang in different environmental conditions. This study used 14 animals. The study was conducted for 30 days. The variables observed were crude fiber digestibility and consumption of drinking water. The results of the t-test statistical analysis showed that crude fiber digestibility and consumption of drinking water provided a difference between goat kacang which were shaded in shade and without shade.From the results of this study it can be concluded that differences in environmental conditions have a significant effect on the level of digestibility of crude fiber and consumption of drinking water from goats.